Effect of Substrate Bias Voltage Amplitude on the Microstructure and Mechanical Properties of NiCrN Films - ZHAO Yanhui, ZHAO Xin, SONG Guihong (Cailiao Baohu)
To further improve the service life of the films in the marine environment，NiCrN films with different substrate bias voltages were deposited on a 304 stainless steel substrate by arc ion plating technology.The effects of the substrate bias voltage on the composition， microstructure， mechanical properties and corrosion resistance of the films were systematically investigated using scanning electron microscopy (SEM)，X-ray diffraction (XRD)， X-ray photoelectron spectroscopy (XPS)， nanoindentation， multifunctional surface properties tester and electrochemical workstation methods.Results showed that the films were primarily composed of metallic Cr， metallic Ni and CrN ceramic phases.As the bias voltage amplitude increased， the thickness and hardness of the films increased， then decreased.When the bias voltage amplitude was－150 V， the hardness reached the maximum value of 2 030 HV.When the substrate bias amplitude was－50 V， the film had the best wear resistance，and the wear rate was the lowest.The corrosion potential of the film shifted positively with the increase of substrate bias amplitude，and the corrosion current density was gradually reduced.When the bias amplitude was－150 V， the corrosion resistance of the film was the best.